Gecko tail regeneration-inspired composite hydrogel scaffolds with “socket-plug” architecture for dynamically programmed repair of infected bone defects - Minglang Zou; Yi Tang; Yongming Wang; Ling Mo; Menghuan Wang; Qing He; Zhenjin Xu; Liu Su; Pengfei Wang; Fang Luo; Da Huang; Jiewei Luo; et al. (Chemical Engineering Journal, 2026)

Intelligent mapping of urban scenic view corridors based on public perception: A case study of Chongqing, China - Yuyue Huang; Junyan Yang; Jiewei Zhang; Jingquan Lin; Zhijian Zhou (Applied Geography, 2026)

Three new terpenes with potential antibacterial and anti-COVID-19 activities from the stems of Eurya chinensis R. Br - Chen Liping; Lin Shaodan; Pan Yongchen; Huijun Liang; Chen Jiayan; Xin Lian; Li Guangying; Xiong Xiubi; Jie Yuan; Jiewei Wu (Natural Product Research, 2026)

Vibration Features of the Aft Shafting Subjected to Semi-Submerged Propeller Hydrodynamic Excitation - Xiaoqing Yin; Junhong Zhang; Jiewei Lin; Huwei Dai; Guopeng Wu (Journal of Marine Science and Engineering, 2026)
To reduce the adverse effects of stern-shaft system vibration on ship performance, this work combined hydrodynamic excitations calculated for a semi-submerged propeller and established a multibody dynamics (MBDs) model of the stern shaft system that included a flexible shaft, propeller, and elastically damped support bearings. The MBDs model’s accuracy was verified through comparison between experimentally identified modal parameters and those computed by the model. It was found that the bearing stiffness and the hydrodynamic excitation frequency collectively determine the vibration amplitude and modal shape of the shaft system, based on an analysis of varied bearing stiffness and damping. Bearing displacement had a significant impact on shafting vibration. And the tie rod with a stiffness of 2.5 × 107 N/m provided a noticeable vibration damping effect. The findings offered theoretical support for mitigating stern-shaft vibration in high-speed vessels subjected to hydrodynamic excitation from semi-submerged propellers.

Exploring the iodine adsorption and deposition behavior: An out-of-pile experiment on accident conditions of lead-bismuth fast reactor - Chenyu Liu; Hanyu Wu; Yuqing Wang; Lili Li; Jiang Zhou; Jiewei Wu; Peng Lin; Muyi Ni (Journal of Hazardous Materials, 2025)

6PPD and 6PPDQ exposure promote the proliferation and migration of non-small cell lung cancer cells through PTEN dysfunction and ARG2-mediated metabolic reprogramming - Chao Wang; Junhao Lin; Jiewei Deng; Xinyan Li; Junqiu Zhai; Yunyun Yang; Tiangang Luan (Journal of Hazardous Materials, 2025)

Optimization of combustion mechanisms and injection strategies for jet disturbance enhanced combustion in heavy-duty diesel engines - Jiayong Wang; Qingyang Ma; Minshuo Shi; Chaojie Jia; Jiewei Lin; Binyang Wu (Fuel, 2025)

Polymerized non-fullerene small molecular acceptor as a versatile electron-transport material for 24.50 % efficiency inverted perovskite solar cells with extended spectral response - Lanyi Yin; Jiewei Yang; Xiao Chen; Yuanhang Lin; Chentong Liao; Qi Wang; Weijian Tang; Wuke Qiu; Xiaopeng Xu; Yihui Wu; Qiang Peng (Chemical Engineering Journal, 2024)

Effects of different ammonia energy ratio on soot formation and oxidation in an ammonia diesel dual-fuel engine - Xiaofeng Wang; Taifeng Shi; Shouying Jin; Minshuo Shi; Jiewei Lin; Binyang Wu (Science of The Total Environment, 2024)

Efflux transport proteins of Tetrahymena thermophila play important roles in resistance to perfluorooctane sulfonate exposure - Mengmeng Wang; Bingyu Song; Tianyu Song; Kailun Sun; Jin He; Jiewei Deng; Ling Fang; Tiangang Luan; Li Lin (Journal of Hazardous Materials, 2023)